ANALISIS PEMAHAMAN KONSELOR DALAM MENGHADAPI PERBEDAAN CULTURE PADA SISWA DI SMPN 1 PANGKALAN LESUNG - M. Fahli Zatrahadi; Firman Firman; Yarmis Syukur (Lembaga penelitian dan pengabdian kepada masyrakat, 2022)
Understanding counselors in dealing with cultural differences in students needs professional competence. The purpose of this study was to analyze the understanding of counselors in dealing with cultural differences in students at SMPN 1 Pangkalan Lesung. Qualitative research uses the following stages: Determine questions, collect data, get data, and report The informants comprised three supervisors at the SMPN 1 Pangkalan Lesung school. The results of the research based on Nvivo coding that there are many multicultural in Indonesia, both in religion, culture, ethnicity, political differences and so on. This is a challenge for counselors in schools to improve professional competence, especially understanding the cross-cultural differences of clients in order to provide understanding to clients who need counseling. Continuing professional development is essential to fulfill these tasks and provide effective services to the school system.